Konseling Pastoral Bagi Anak Remaja Yang Kurang Mampu Dalam Segi Finansial - Yonathan Deivid Oroh (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2024)
Poverty is a reality or social fact in human society from ancient times to the current post-modern era. Poverty was already experienced by those who lived in Bible times and also by believers in our era. It can be said that poverty is an eternal human problem. In this article the focus of writing will be on the problem of poverty which is financial in the form of material. In this article the author will convey a number of things as follows: an overview of adolescents whose parents are financially disadvantaged and how to motivate them by way of resolution through pastoral counseling